Local tumor control probability to evaluate an applicator‐guided volumetric‐modulated arc therapy solution as alternative of 3D brachytherapy for the treatment of the vaginal vault in patients affected by gynecological cancer. (4th March 2013) - Pedicini, Piernicola; Strigari, Lidia; Caivano, Rocchina; Fiorentino, Alba; Califano, Giorgia; Nappi, Antonio; Improta, Giuseppina; Storto, Giovanni; Cozzolino, Mariella; Chiumento, Costanza; Fusco, Vincenzo; Vavassori, Andrea; et al.
Abstract : The purpose of this study was to evaluate the applicator‐guided volumetric‐modulated arc therapy (AGVMAT) solution as an alternative to high‐dose‐rate brachytherapy (HDR‐BRT) treatment of the vaginal vault in patients with gynecological cancer (GC). AGVMAT plans for 51 women were developed. The volumetric scans used for plans were obtained with an implanted CT‐compatible vaginal cylinder which provides spatial registration and immobilization of the gynecologic organs. Dosimetric and radiobiological comparisons for planning target volume (PTV) and organs at risk (OARs) were performed by means of a dose‐volume histogram (DVH), equivalent uniform dose (EUD), and local tumor control probability (LTCP). In addition, the integral dose and the overall delivery time, were evaluated. The HDR‐BRT averages of EUD and minimum LTCP were significantly higher than those of AGVMAT. Doses for the OARs were comparable for the bladder and sigmoid, while, although HDR‐BRT was able to better spare the bowel, AGVMAT provided a significant reduction of d 2 cc, d 1 cc, and d max ( p < 0.01 ) for the rectum. AGVMAT integral doses were higher than HDR‐BRT with low values in both cases. Delivery times were about two or three times higher for HDR‐BRT with respect to the single arc technique (AGVMAT1) and dual arc technique (AGVMAT2), respectively. The applicator‐guided volumetric‐modulated arc therapy seems to have the potential of improving rectum avoidance. However, brachytherapy improves performance in terms of PTV coverage, as demonstrated by a greater EUD and better LTCP curves. PACS number: 87